Impact Assessment Mechanisms in the Framework of the Protection of Fundamental Rights. A comparative perspective analysis on the field of artificial intelligence (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This paper seeks to examine the role of impact assessment mechanisms as instruments for the protection of fundamental rights within the regulatory frameworks governing emerging technologies, with specific reference to artificial intelligence systems. It will first consider the increasing prominence of impact assessments as a governance tool for artificial intelligence, highlighting their dual function: on the one hand, to safeguard the diverse interests implicated in the deployment of intelligent systems, and on the other, to prevent undue limitations on the development and application of such technologies. Subsequently, the paper will conduct a comparative analysis of the design and implementation of impact assessment mechanisms in Canada, the United States, and the European Union, with particular emphasis on their capacity to uphold fundamental rights and the nature of the entities entrusted with their execution within the regulation of artificial intelligence.
Keywords: Fundamental rights; artificial intelligence; impact assessment; Canada; United States; European Union